Pediatric Migraine: Abortive Management in the Emergency Department. Issue 2 (29th October 2013) - Sheridan, David C.; Spiro, David M.; Meckler, Garth D.
<x xml:space="preserve">Abstract</x> Studies suggest that headache accounts for approximately 1% of pediatric emergency department (ED) visits. ED physicians must distinguish between primary headaches, such as a tension or migraine, and secondary headaches caused by systemic disease including neoplasm, infection, or intracranial hemorrhage. A recent study found that 40% of children presenting to the ED with headache were diagnosed with a primary headache, and 75% of these were migraine. Once the diagnosis of migraine has been made, the ED physician is faced with the challenge of determining appropriate abortive treatment. This review summarizes the most recent literature on pediatric migraine with an emphasis on diagnosis and abortive treatment in the ED.